Heat stability of high-protein ultrafiltration retentate: Effect of concentration factor and stabilizing salts - Meena, Ganga Sahay; Singh, Ashish Kumar; Gupta, Vijay Kumar; Gujral, Harleen Kaur; Malhotra, Rashmeet Kaur (Indian Journal of Dairy Science, 2021)
Pasteurized cow skim milk (PCSM, 1×) was concentrated using ultrafiltration (UF) from 2 ×-7 × concentration factor (CF) to obtain retentates with different protein to total solids (TS) ratio. Alteration in chemical make-up led to poor thermal stability in UF retentates. Therefore, this study was aimed to investigate the changes in permeate flux, chemical composition, pH, viscosity and heat coagulation time (HCT) of UF/DF retentates as a function of CF. Impact of high-shear (20,000 rpm/ 5 min), diafiltration (DF) with 150mM NaCl solution and stabilizing salts on HCT of high-protein 7×UF retentates were also evaluated. With increase in CF; TS, protein, fat, ash, calcium contents and viscosity increased significantly (p<0.05), while permeate flux, lactose content, pH and HCT of retentates significantly decreased (p<0.05). Poor HCT (1 min) of 7×UF retentate was significantly increased (p<0.05) up to 60 min by addition of stabilizing salts (NaH2PO4, Na2HPO4 and Na3C6H5O7). Correlation was established between chemical constituents, pH, viscosity, HCT, permeate flux and concentration factor. Overall, this investigation established that identification of correct stabilizing salts via HCT-pH curve of PCSM and their appropriate addition converted thermally unstable (poor HCT) high-protein (7× UF) retentates to thermally stable product. Hence, they could be now explored in number of food applications.